2021
DOI: 10.1002/anie.202106329
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes with Water as a pH‐Responsive Functionality for Targeting of Acidic Tumor and Infection Sites

Abstract: Al ipid named DCPAw as synthesized under microwave-assisted heating. DCPAp ossesses ap yridine betaine,h ydrophilic group that can be complexed with water through hydrogen bonding (DCPA-H 2 O). DCPA-H 2 Ol iposomes became protonated relatively fast already at pH < 6.8, due to the high HOMO binding energy of DCPA-H 2 O. In murine models,D CPA-H 2 Ol iposomes had longer blood circulation times than natural DPPC or cationic DCPM liposomes,w hile after tail-vein injection DCPA-H 2 Ol iposomes targeted faster to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…The use of abdominal biofilms with an intra-vital window to visualize biofilm targeting and eradication by nano-antimicrobials has only been applied for pH-responsive, self-targeting micelles [ 35 ] and liposomes [ 36 ], but not yet for magnetic targeting of cascade-reaction containers. Interestingly, despite the problems in finding magnetic field conditions for evenly distributing magnetic cascade-reaction containers over the depth of a biofilm using a one-directional, single magnet ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of abdominal biofilms with an intra-vital window to visualize biofilm targeting and eradication by nano-antimicrobials has only been applied for pH-responsive, self-targeting micelles [ 35 ] and liposomes [ 36 ], but not yet for magnetic targeting of cascade-reaction containers. Interestingly, despite the problems in finding magnetic field conditions for evenly distributing magnetic cascade-reaction containers over the depth of a biofilm using a one-directional, single magnet ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that particularly zwitterionbased platforms adsorb very little protein. 19,29 However, often these in vitro experiments are done either with selected proteins, 30,31 diluted plasma, 8,32 or in absence of flow. 33,34 Accordingly, the in vivo experiments outlined in Fig.…”
Section: Self-targeting Of Infectious Sitesmentioning
confidence: 99%
“…From the above mini-review, it can be concluded that all requirements set to a self-targeting platform for nano-antimicrobials or 8 poly(ethylene oxide)-blockpoly(acrylic acid) 23 1,2-dioleoyl-3-trimethylammonium-propane, 24 and (b-amine ester), 16 respectively. (b) Zeta potentials of different zwitterionbased platforms.…”
Section: Clinical Merits Of Self-targeting Versus Targeting Platforms...mentioning
confidence: 99%
“…24 Viral vectors are restricted in clinical applications due to their safety issues. Non-viral vectors, which have been widely developed and adopted due to their low virulence and non-immunogenicity, [25][26][27] include cationic liposomes, 28 polyethyleneimine (PEI) 29 and poly (β-amino ester) (PBAE). 30,31 Among non-viral vectors, PBAEs are a widely used type of cationic polymer gene carrier with excellent biocompatibility, good biodegradability, easy production, and low cost.…”
Section: Introductionmentioning
confidence: 99%